IMPROVING STUDENTS` SKILLS IN WRITING DESCRIPTIVE TEXTS BY USING GROUP DISCUSSION ONLINE: A STUDY AT SMPN 15 MALANG - Istichomah Isti Fania (Graduate Program, University of Islam Malang, 2021)
Abstract: This study is to describe how Online Group Discussion can improve the seventh-grade students` writing skill in descriptive text. This study was a Classroom Action Research (CAR) in two cycles process starting from making lesson plan, implementation, observation, and reflection. The quantitative data were obtained from the test and questionnaire; the qualitative data ware obtained from observation of the teaching and learning process, the students’ answers, and the researcher’s field-notes. After the implementation of the plan in cycle 2, the criteria of success were fulfilled. The mean score is 77.2 better than first test, 75.8. it means that the writing descriptive text of the students in the seventh grade students at SMPN 15 Malang improve. Based on these results, it is recommended that teachers apply online group discussion in teaching descriptive text. Key words: Writing Skill, Descriptive Text, Online Group Discussion